Efektivitas Antifungi Ekstrak Daun Patikan Kebo (Euphorbia hirta) Terhadap Jamur Penyebab Kandidiasis (Candida albicans) - Zulkarnain Zulkarnain; Cut Muthiadin; Fatmawati Nur; Rusmadi Rukmana (Al-Hayat: Journal of Biology and Applied Biology, 2019)
Candidiasis is an infectious disease caused by the fungus Candida albicans. This  study aims to determine the effect of patikan kebo (Euphorbia hirta) leaf extract in inhibiting the growth of C. albicans. This research is an experimental study which was compiled using a Completely Randomized Design (CRD) by giving Patikan Kebo (E. hirta) leaf extract  in several concentrations, the concentrations of 40%, 45%, 50%, 55%, and 60% and controls (aquadest) and C. albicans mushroom with three repetitions. The parameters measured are the amount of inhibitory diameter formed around the paper discs in the 24 hour and 48 hour period. D ata obtained with three repetitions and observations of 24 hours and 48 hours showed that giving patikan kebo leaf extract in several types of concentration had an effect on inhibiting the growth and fungi of C . albicans. Furthermore, the data obtained were analyzed using analysis of variance (F-test) at the level of α 0.05 and continued using the Smallest Significant Difference (LSD) α 0.05 where the results showed that the giving of patikan kebo extract significantly affected the microbial growth test (C. albicans), where the higher the concentration of patikan kebo leaf extract, the greater the inhibition zone formed around the paper disk.